2019
DOI: 10.3390/cancers11040475
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Inhibitors Exert Anti-Myeloma Effects through Multiple Modes of Action

Abstract: HDACs are critical regulators of gene expression that function through histone modification. Non-histone proteins and histones are targeted by these proteins and the inhibition of HDACs results in various biological effects. Moreover, the aberrant expression and function of these proteins is thought to be related to the pathogenesis of multiple myeloma (MM) and several inhibitors have been introduced or clinically tested. Panobinostat, a pan-HDAC inhibitor, in combination with a proteasome inhibitor and dexame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…Transcriptional regulation of HSP90 expression is mainly controlled by HSFs (heat shock factors), which bind to HSE (heat shock element) located in the promoter region of HSP90 [31,32]. HDAC6 (histone deacetylase 6)-mediated regulation of HSP90 stability, posttranslational modifications of cytosolic HSP90 that include phosphorylation, acetylation, methylation, ubiquitylation and S-nitrosylation have been extensively discussed elsewhere [30,[33][34][35].…”
Section: Hsp90: Structure and Regulation Of Activitymentioning
confidence: 99%
“…Transcriptional regulation of HSP90 expression is mainly controlled by HSFs (heat shock factors), which bind to HSE (heat shock element) located in the promoter region of HSP90 [31,32]. HDAC6 (histone deacetylase 6)-mediated regulation of HSP90 stability, posttranslational modifications of cytosolic HSP90 that include phosphorylation, acetylation, methylation, ubiquitylation and S-nitrosylation have been extensively discussed elsewhere [30,[33][34][35].…”
Section: Hsp90: Structure and Regulation Of Activitymentioning
confidence: 99%
“…For instance, bortezomib could be suitable for combination with CKD-581. It has also been reported that HDAC inhibitors enhance the accumulation of misfolded proteins induced by proteasome inhibitors [40,41]. Bruton's tyrosine kinase (BTK) inhibitor has also been proposed as a combination therapy to HDAC inhibitor treatment, to overcome acquired resistance in lymphoma [42].…”
Section: Discussionmentioning
confidence: 99%
“…HDAC6 may regulate the expression of PD-L1 through the transcription factor STAT3, but the molecular mechanism of how HDAC6 regulates PD-1 is still unclear (Lienlaf et al, 2016). In addition, ACY-241 can enhance anti-MM tumor immune activity by increasing the expression of surface antigens B7 and MHC on dendritic cells and MM cells, promoting the proliferation of CD4 + /CD8 + T cells and reducing the number of MM cells, regulatory T cells, and myeloid-derived suppressor cells (Bae et al, 2018;Imai et al, 2019).…”
Section: Hdac6 Inhibitors Inhibit the Expression Of C-myc Thereby Sumentioning
confidence: 99%
“…HDAC6 plays an important role in this process by binding to polyubiquitinated proteins and recruiting protein cargoes to dynein, which are then transported along microtubules to aggregates ( Mishima et al., 2015 ; Huang et al., 2019 ). The HDAC6 inhibitors ricolinostat and WT161 inhibited protein aggregate formation in vivo , and combined use with proteasome inhibitors further resulted in excessive accumulation of misfolded/unfolded proteins, ER stress, and caspase-dependent apoptosis ( Santo et al., 2012 ; Hideshima et al., 2016 ; Vogl et al., 2017 ; Imai et al., 2019 ) ( Figure 1C ).…”
Section: Multiple Myeloma (Mm)mentioning
confidence: 99%